Knowledge Production at the Cutting Edge?: A Content Analysis of AERC Papers from 1995-2005 - Lisa Troy (Adult Education Research Conference, 2006)
Adult Education Research Conference presentations are analyzed from 1995 through 2005 for content and authorship gender. This analysis compares findings from this time period with findings from the 1970’s and the late 1980’s.
Keywords: Content analysis; adult education research conference